2006
DOI: 10.1113/jphysiol.2005.099770
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of cross‐bridge kinetics on myosin light chain isoforms in rabbit and rat skeletal muscle fibres

Abstract: Cross-bridge kinetics underlying stretch-induced force transients was studied in fibres with different myosin light chain (MLC) isoforms from skeletal muscles of rabbit and rat. The force transients were induced by stepwise stretches (< 0.3% of fibre length) applied on maximally Ca 2+ -activated skinned fibres. Fast fibre types IIB, IID (or IIX) and IIA and the slow fibre type I containing the myosin heavy chain isoforms MHC-IIb, MHC-IId (or MHC-IIx), MHC-IIa and MHC-I, respectively, were investigated. The MLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 62 publications
(92 reference statements)
1
23
0
Order By: Relevance
“…It is an open question if the N-terminal extension contributes to the slowing effect of MLC1s on myosin head kinetics. The fact that the MLC1f/MLC3f ratio does not influence the myosin head kinetics [5] excludes this possibility at first glance. However, studies on heart preparations showed that the myosin head kinetics is decelerated by the interaction of the N-terminal extension of the ventricular alkali MLC isoform MLC1v with the actin filament [35,37].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…It is an open question if the N-terminal extension contributes to the slowing effect of MLC1s on myosin head kinetics. The fact that the MLC1f/MLC3f ratio does not influence the myosin head kinetics [5] excludes this possibility at first glance. However, studies on heart preparations showed that the myosin head kinetics is decelerated by the interaction of the N-terminal extension of the ventricular alkali MLC isoform MLC1v with the actin filament [35,37].…”
Section: Discussionmentioning
confidence: 89%
“…The presence of MLC1s implicates a reduction of either MLC1f or MLC3f because of substitution. Therefore, in principle, the observed differences in kinetics could be due to the varying MLC1f/ MLC3f ratio, but this was excluded in a former study showing that a varying MLC1f/MLC3f ratio does not influence myosin head kinetics [5]. Therefore, it can be concluded that MLC1s causes a slowing of the myosin head kinetics in type IIA fibres.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Gene expression changes for other muscle contractile proteins, as well. Myosin regulatory light chains regulate the kinetics of force transmission of the specific MHC isoforms by modulating the binding of fast and slow myosin light chain (MLC) isoforms [27][28]. In the current study, the MRLC3 and myosin light polypeptide 6B (MYL6B) genes were significantly down-regulated in the paretic leg after chronic stroke.…”
Section: Discussionmentioning
confidence: 62%